Acetabular Reconstruction Using Multiple Porous Tantalum Augments: Three-Quarter Football Augment - C. H. Ansorge; M. Ohlmeier; T. M. Ballhause; T. Gehrke; M. Citak; M. Lee (Case Reports in Orthopedics)
Reconstruction of a large acetabular bone defect is a complex problem in revision hip arthroplasty. The authors report a novel method of reconstructing an uncontained acetabular defect (Paprosky type IIIb) using multiple tantalum augments. A 73-year-old female patient presented to our institution with a chronically dislocated primary left total hip arthroplasty with radiographs demonstrating migration of acetabular component and formation of pseudoarthrosis within the left ilium. Extensive arthrolysis and anatomic reconstruction of the acetabular bone defect were performed using the novel method of multiple tantalum augments. Postoperatively, recovery was initially complicated by multiple dislocations requiring an exchange to an elevated liner, however subsequently achieved good function.